2013
DOI: 10.1590/s1676-06032013000200025
|View full text |Cite
|
Sign up to set email alerts
|

As abelhas do gênero Xylocopa Latreille (Xylocopini, Apidae) do Estado de São Paulo, Brasil

Abstract: This study contributes to the knowledge about the diversity of bees belonging to the genus Xylocopa Latreille, 1802 of the São Paulo State through a compilation of taxonomic and biological information. Identification keys are presented for the four subgenera (Dasyxylocopa Hurd & Moure, 1963; Neoxylocopa Michener, 1954; Schonnherria Lepeletier, 1841 and Stenoxylocopa Hurd & Moure, 1960) and for the 22 species recorded for the state, beyond the available data on its biology, plants visited and geographic occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…However, studies showed that the species can guarantee natural pollination in more anthropized areas of São Paulo and other Brazilian States (Camillo 2003;Oliveira-Filho and Freitas 2003). Moreover, Marchi and Santos (2013), in a oristic survey of species visited by Xylocopa carpenter bees in São Paulo State, reported that X. frontalis visits a wide variety of angiosperms in urban and agricultural areas, including T. stans, D. regia, B. orellana and C. juncea, these species being present in our study site.…”
Section: Pollen Viabilitymentioning
confidence: 99%
“…However, studies showed that the species can guarantee natural pollination in more anthropized areas of São Paulo and other Brazilian States (Camillo 2003;Oliveira-Filho and Freitas 2003). Moreover, Marchi and Santos (2013), in a oristic survey of species visited by Xylocopa carpenter bees in São Paulo State, reported that X. frontalis visits a wide variety of angiosperms in urban and agricultural areas, including T. stans, D. regia, B. orellana and C. juncea, these species being present in our study site.…”
Section: Pollen Viabilitymentioning
confidence: 99%
“…In contrast, these bees are often cited as nectar robbers of large flowers by perforating the corolla tubes from the outside with their stiff galeae (e.g. Correia et al 2006;Carvalho et al 2007;Milet-Pinheiro & Schlindwein 2008;Marchi and Alves-dos-Santos 2013;Schlindwein et al 2014). They do not pollinate these flowers because they do not contact the anthers during visits (Milet-Pinheiro and Schlindwein 2009, plus the pollen from these illegitimate visits does not appear in larval provisions.…”
Section: Introductionmentioning
confidence: 99%
“…Algumas características são comuns a este gênero, a exemplo da coloração preta e brilhante (Marchi & Santos, 2013).…”
Section: Introductionunclassified